THE IMAGE SERVING THE ELUCIDATION OF VOCABULARY AND THE UNDERSTANDING OF THE HISTORY TEXT AMONG LEARNERS OF THE THIRD YEAR OF SECONDARY SCHOOL IN THE ALGERIAN CONTEXT - Said MAHMOUDI; Dalila LAKOUIS (Езиков свят)
Resorting to the use of images in French as a foreign language classroom for third-year secondary learners allows the teacher to explain the vocabulary related to history within a didactic framework that serves to use visual aids in the Algerian school context. The objective of this study is twofold: on the one hand, it helps the learner to extract and identify the meaning of the word through the image, and on the other hand, it serves to elucidate the vocabulary of historical writing despite the polysemous nature of certain images used in the enrichment or acquisition of the studied vocabulary. To this end, the learners find themselves in a situation to develop their interpretative skills. They create connections between the received meaning and its illustration based on the theme presented in a historical text. The teacher's role in the classroom is crucial through the planning of vocabulary study sessions based on two approaches: lexical and grammatical. In summary, the use of images contributes to the teaching of historical vocabulary and encourages learners to engage deeply with this type of text through the contextualization of information conveyed in a specific context and the creation of a dictionary illustrating the expressions and key terms studied in historical writing.